Predicting treatment response to vancomycin using bacterial DNA load as a pharmacodynamic marker in premature and very low birth weight neonates: A population PKPD study - Samb, Amadou; De Kroon, Rimke; Dijkstra, Koos; Van Den Brand, Marre; Bos, Martine; Van Den Dungen, Frank; Veldkamp, Agnes; Wilhelm, Bram; De Haan, Timo R.; Bijleveld, Yuma A.; Tutu Van Furth, Marceline; Savelkoul, Paul; et al. (Frontiers in Pharmacology, 2023)
Background: Whilst positive blood cultures are the gold standard for late-onset sepsis (LOS) diag-nosis in premature and very low birth weight (VLBW) newborns, these results can take days and ear-ly markers of possible treatment efficacy are lacking. The objective of the present study was to inves-tigate whether the response to vancomycin could be quantified using bacterial DNA loads (BDL) determined by real-time quantitative polymerase chain reaction (RT-qPCR). Methods: VLBW and premature neonates with suspected LOS were included in a prospective observational study. Serial blood samples were collected to measure BDL and vancomycin concentrations. BDL were measured with RT-qPCR, whereas vancomycin concentrations were measured by LC-MS/MS. Population pharmacokinetic-pharmacodynamic modeling was performed with NONMEM. Results: Twenty-eight patients with LOS treated with vancomycin were included. A one-compartment model with post-menstrual age (PMA) and weight as covariates was used to describe the time PK-profile of van-comycin concentrations. In 16 of these patients time profiles of BDL could be described with a pharmacodynamic turnover model. The relationship between vancomycin concentration and first-order BDL elimination was described with a linear effect model. Slope S increased with rising PMA. In 12 patients no decrease in BDL over time was observed, which corresponded with clinical non-response. Discussion: BDLs determined through RT-qPCR were adequately described with the de-veloped population PKPD model and treatment response to vancomycin using BDL in LOS can be assessed as early as 8 hours after treatment initiation.